Eve isn't evil: feminist readings of the Bible to upend our assumptions - Parker, Julie Faith (Baker Academic, 2023)
Intro -- Endorsements -- Half Title Page -- Title Page -- Copyright Page -- Dedication -- Autobiography of Eve -- Contents -- 1. In the Beginning . . . -- 2. Eve Isn't Evil-Why I Love Her and You Should Too -- 3. Think Your Family's a Mess? Biblical Families R Us -- 4. Sex Workers, Slaughters, and Deities without Borders -- 5. Profit from Prophecy -- 6. The job of Job -- 7. Guns and Psalms -- 8. Song of Songs in Sing Sing -- 9. My Favorite Feminist Jew -- 10. Curious, Like Eve? Learn More -- Appendix 1: Bible Basics -- Appendix 2: Resources for Further Exploration -- Acknowledgments -- Abbreviations -- Bibliography -- Scripture Index -- Subject Index -- Back Cover.